Antioxidant Activity of Dominant Plants Species in Obat Pahit from Lingga Malay Ethnic in Riau Archipelago - Fitmawati Fitmawati; Nery Sofiyanti; Rodesia Mustika Roza; Isnaini Isnaini; Yulisa Resti Irawan; Dhaniel Ridho Winata; Awal Prichatin Kusumo Dewi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Obat Pahit is a potion that has been long commonly consumed by Lingga Malay society for generations as stamina keeper. The most dominant plants found in the packaging of the Obat Pahit were namely Bauhunia semibifida, Cnestis palala and Penawa Root (3 species). This research aimed to investigate and determine activity of antioxidant contents in Obat Pahit from five Traditional Medicine Practitioners (TMPs) in the district of Lingga. The tested samples were mashed then being soaked into 2 types of solvent: distilled water and methanol, containing HCl 1%. DPPH method was also used in this research. Quantitatively antioxidant activity test of Obat Pahit from the five TMPs by using methanol solvent had extremely highest activity compared to the distilled water solvent. The test, using TLC plate by spraying the extract from three dominant plants with 0.1 mM of DPPH solution, produced a pale-yellow spots at a wavelength of 366 nm. On the other hand, the test using HPLC at wavelengths of 230 nm and 280 nm showed the presence of two dominant secondary metabolites contents: flavonoid and phenolic. IC50 (ppm) of Bauhinia semibifida (6.6247), Penawa Root (5.0124) and Cnestis palala (5.9968) were much lower than IC50 of mangosteen’s rind (41.7675), vitamin C (6.6612) and Stimuno drug (8.333). This antioxidant analysis has not been reported previously. This proof contributed greatly to uncovering potentially native natural resources as an indigenous Indonesian drug which is expected to decrease dependence on imported drugs especially imunomodulator, antihypertensive, antidiabet etc. This research would be beneficial and excellent manifestation for the development of natural antioxidant-based medicines from traditional knowledge of Indonesia’s local ethnicities.